Chimeric models to analyze human neuron and astroglia responses in Alzheimer's disease: Molecular and cell biology/stem cells, iPS cells. (7th December 2020) - Arranz, Amaia M.; Preman, Pranav; T.C.W., Julia; Snellinx, An; Calafate, Sara; Thal, Dietmar Rudolf; Goate, Alison M.; De Strooper, Bart
Abstract: Background: We have previously generated a chimeric model of Alzheimer´s disease (AD) by transplanting human pluripotent stem cell (PSC)‐derived neurons into the brain of a rodent model of AD. Remarkably, human neurons integrate efficiently into the mouse brain and show main pathological hallmarks of AD such as abnormal Tau phosphorylation, pathological Tau conformational changes and major degeneration and cell loss. However, PSC‐derived mouse neurons transplanted into the mouse brain are not able to recapitulate main AD hallmarks, which reveals a selective vulnerability of human neurons to the amyloid pathology and associated neuroinflammation. Method: On follow‐up studies, we are generating a chimeric model of AD using a similar experimental approach and transplanting human PSC‐derived astrocytes into the brain of AD mice. Result: Human astrocytes also integrate in the mouse host brain and mature in a cell‐autonomous way maintaining their human‐specific properties. Interestingly, human astrocytes interact with Aβ plaques showing differential morphological responses. Conclusion: This novel data highlights the importance of studying both human neurons and glia cells on the context of AD.